The Concepts of Forest Governance Practices at Site Level in Indonesia - Tampubolon, Longgak Arianto (FIA UB, 2018)
This paper aims to explore the concept of forest governance practices at site level in Indonesia. It carried out content analysis by analyzing governmental regulations and related case studies from various authors. Indonesia recognizes four kinds of forest governance at site level such as hutan tanaman rakyat, hutan desa, hutan kemasyarakatan and kemitraan. All forms need local community involvement. The former three have connection with government, meanwhile the latter involves forest-related license. Some studies show their positive impact not only for community livelihoods but also for forest ecosystem. However, the common problems emerged from these implementations are characterized by weak local capability and bureaucratic process.